2022
DOI: 10.15419/bmrat.v9i2.729
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for early complications of acute myocardial infarction in patients with type 2 diabetes mellitus

Abstract: Introduction:Early complications of acute myocardial infarction (AMI) are one of the leading causes of death among patients with type 2 diabetes mellitus (DM). Clinical and laboratory characteristics and noninvasive methods need to be integrated to better identify early complications of AMI and further develop a treatment strategy. The aim of the study was to predict the development of early complications after AMI in type 2 DM patients, which could improve the quality of preventive and curative measures for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Moreover, hypertension, DM, increased systolic blood pressure, along with higher glucose levels have been believed to be associated with an increase in FABP4 circulating levels (Tsai et al, 2021). Finally, the authors have revealed lower serum concentration of CTRP3 in CHD patients, especially in acute MI (Si et al, 2020;Koteliukh et al, 2022). Therefore, the constructed prognostic model predicted the probability of the recurrent MI absence with a high accuracy of 98.4% and the probability of the recurrent MI with an accuracy of 92.3% in patients with 2 types DM within a year based on the measurement findings on the 1st and 14th day of observation.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, hypertension, DM, increased systolic blood pressure, along with higher glucose levels have been believed to be associated with an increase in FABP4 circulating levels (Tsai et al, 2021). Finally, the authors have revealed lower serum concentration of CTRP3 in CHD patients, especially in acute MI (Si et al, 2020;Koteliukh et al, 2022). Therefore, the constructed prognostic model predicted the probability of the recurrent MI absence with a high accuracy of 98.4% and the probability of the recurrent MI with an accuracy of 92.3% in patients with 2 types DM within a year based on the measurement findings on the 1st and 14th day of observation.…”
Section: Resultsmentioning
confidence: 96%
“…Low serum levels of CTRP3 were observed in patients with HF and reduced LV EF [25]. The authors underlined decreased CTRP3 serum levels in patients with CAD, especially in AMI [26], [27].…”
Section: Discussionmentioning
confidence: 99%